Enterprise Interoperability VII Enterprise Interoperability in the Digitized and Networked Factory of the Future - Mertins, Kai.; Jardim-Gonçalves, Ricardo; Popplewell, Keith; Mendonça, João P.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
A concise reference to the state of the art in systems interoperability, Enterprise Interoperability VII will be of great value to engineers and computer scientists working in manufacturing and other process industries and to software engineers and electronic and manufacturing engineers working in the academic environment. Furthermore, it shows how knowledge of the meaning within information and the use to which it will be put have to be held in common between enterprises for consistent and efficient inter-enterprise networks. Over 30 papers, ranging from academic research through case studies to industrial and administrative experience of interoperability show how, in a scenario of globalised markets, where the capacity to cooperate with other organizations efficiently is essential in order to remain economically, socially and environmentally cost-effective, the most innovative digitized and networked enterprises ensure that their systems and applications are able to interoperate across heterogeneous collaborative networks of independent organizations. This goal of interoperability is essential, not only from the perspective of the individual enterprise but also in the business structures that are now emerging, such as complex collaborating networks of suppliers and customers, virtual enterprises, interconnected organisations or extended enterprises, as well as in mergers and acquisitions. Establishing efficient and relevant collaborative situations requires the management of interoperability from a dynamic point of view: a relevant and efficient collaboration of organizations may require adaptation to remain in line with changing objectives, evolving resources, unexpected events, etc. Many of the papers contained in this, the eighth volume of Proceedings of the I-ESA Conferences have examples and illustrations calculated to deepen understanding and generate new ideas. The I-ESA'16 Conference from which this book is drawn was organized by the Escola de Engenharia da Universidade do Minho, on behalf of the European Virtual Laboratory for Enterprise Interoperability (INTEROP-VLab) and Interop VLab Portuguese Pole.
Part I: Introduction -- An Interoperable Cloud Environment of Manufacturing Control System -- A New Framework for Strategic Risk Analysis in a Global Pump Manufacturing Network -- Cloud and Services Testing Applied in Manufacturing -- A Self Sustainable Approach for IoT Services Provisioning -- Part II: Modelling the Enterprise Interoperability -- Requirement Pattern Elicitation Approach of Massive Customers in Domain Oriented Service Requirement -- Semantic Data Integration Approach for the Vision of a Digital Factory -- Negotiation Coordination Model for Supporting Enterprise Interoperability -- Part III: Semantics for Enterprise Interoperability -- The Systems Development Life Cycle to Facilitate Progression Towards Semantic and Organizational Interoperability for Healthcare System -- Performance Oriented Decision Making to Guide Web Service Lifecycle -- Profiling Based on Music and Physiological State -- Part IV: Architectures and Frameworks for Interoperability -- Automated Process Model Generation for Internet of Things Oriented Enterprise Systems -- Use of Big Data for Continuous Interoperability in Crisis Management -- Weaving Trending, Costing and Recommendations Using Big Data Analytics: An Enterprise Capability Evaluator -- The Industry Cockpit Approach: A Framework for Flexible Real-time Production Monitoring -- Part V: Services for the Enterprise Interoperability -- iFloW: An Integrated Logistics Software System for Inbound Supply Chain Traceability -- Qualitative Evaluation of Manufacturing Software Units Interoperability Using ISO 25000 Quality Mode -- Process Modeling Approach for the Liquid-Sensing Enterprise -- Part VI: Ontologies and Concepts for Enterprise Interoperability -- A MetaMeta Level Formal Manufacturing Ontology for Meta Level Production Methods -- Towards an Interoperable Decision Support Platform for Eco-labeling Process -- Framework of Design Principles and Standards for Enterprise Interoperability Service Utilities -- Part VII: Industrial Implementation of Enterprise Interoperability -- Requirements Engineering Using Serious Games -- Knowledge-based System to Enhance Coordination of Hospital Practitioners: A Case Study -- Towards a Flexible Gamification Model for an Interoperable E-learning BP Simulation Platform -- Part VIII: Collaborative Supply Networks Interoperability -- Towards a Methodology to Support the Strategies Alignment Process in Collaborative Networks -- Meta-modeling of Collaborative Supply Chain -- Seamless Interrelation Between Business Strategies and Tactical Planning -- A Competition Model for the Offer: An Experiment of Management Simulation.
Keywords: Industrial Management; Telecommunication; Electronic data processing -- Management; Software engineering; Industrial Management; Communications Engineering, Networks; IT Operations; Software Engineering